Digital vs. Freehand Anterior Single-Tooth Implant Restoration. (23rd October 2020) - Baldi, D.; Colombo, J.; Motta, F.; Motta, F. M.; Zillio, A.; Scotti, N.
Abstract : Replacing a single tooth in the anterior maxilla is one of the greatest challenges in dentistry. Both functional and aesthetic results are to be strictly pursued. Planning and executing such a case through a totally digital methodology eventually guarantee many advantages, above all patient's operative and postoperative comfort. To ascertain this, a BOP analysis was performed which allowed us to evaluate soft tissues health, and more; crestal bone resorption was measured to evaluate hard tissues stability. This assumption was studied through four cases in which patients were alternatively treated with analogic and digital techniques. Four homogeneous patients were recruited. They all needed to extract one of the upper incisors, due to different clinical reasons, and then to replace it with an implant. Each patient was treated with an immediate postextractive implant which was immediately loaded, and finally, analogical and digital techniques were compared. All patients underwent a preoperative CBCT examination. After surgery, patients were checked by the surgeon after 10 days and one month to evaluate the progress of healing and to exclude any prosthetic problem. At 6 months (T1), one year (T2), and three years (T3), intraoral x-rays were performed using customized centring devices, according to the parallel beam technique. All data have been collected in a table and statistically processed; mean and standard deviation were measured. All patients entered an oral hygiene program with six months recall. Dental hygienist checked the BOP at T1, T2, and T3. At every step, similar levels of BOP were recorded. About interproximal bone loss, all patients showed an initial moderate loss (between T1 and T2), followed by stable values between T2 and T3. Despite the important limitations of a study with few cases, these results show a similar outcome comparing digital and analogical methods.